Weierstrass points on modular curves X0(N) fixed by the Atkin–Lehner involutions. Issue 1 (12th August 2021) - Bojakli, Mustafa; Sankari, Hasan
Abstract : Purpose: The authors have determined whether the points fixed by all the full and the partial Atkin–Lehner involutions W Q on X 0 ( N ) for N ≤  50 are Weierstrass points or not. Design/methodology/approach: The design is by using Lawittes's and Schoeneberg's theorems. Findings: Finding all Weierstrass points on X 0 ( N ) fixed by some Atkin–Lehner involutions. Besides, the authors have listed them in a table. Originality/value: The Weierstrass points have played an important role in algebra. For example, in algebraic number theory, they have been used by Schwartz and Hurwitz to determine the group structure of the automorphism groups of compact Riemann surfaces of genus g ≥  2. Whereas in algebraic geometric coding theory, if one knows a Weierstrass nongap sequence of a Weierstrass point, then one is able to estimate parameters of codes in a concrete way. Finally, the set of Weierstrass points is useful in studying arithmetic and geometric properties of X 0 ( N ).